Studies on canning Psenopsis cyanea - Vijayan, P.K., Balachandran, K.K. and (Fishery Technology, 2021)
Suitability of Psenopsis cyanea, a deep sea fish caught on board FORV Sagar Sampada from a depth of 350m off Cochin for processing into canned product was studied. The fish having high fat content around 52% (DWB) and white attractive meat renders itself well for canning yielding a product good in organoleptic characteristics. However to have a presentable appearance to the product the fish has to be skinned prior to canning. Gentle agitation of P. cyanea in 0.25% aqueous solution of lactic acid at ambient temperature for 15 min followed by thorough washing yields skinless fish. Fish suffers around 8% (DWB) fat loss during skinning. Fish canned in natural style and in brine have better organoleptic characteristics initially. On storage they develop slight rancidity. Fish canned in oil maintains the characteristics over a longer period.